Transcriptomes of human primary skin fibroblasts of healthy individuals reveal age‐associated mRNAs and long noncoding RNAs - Tsitsipatis, Dimitrios; Martindale, Jennifer L.; Mazan‐Mamczarz, Krystyna; Herman, Allison B.; Piao, Yulan; Banskota, Nirad; Yang, Jen‐Hao; Cui, Linna; Anerillas, Carlos; Chang, Ming‐Wen; Kaileh, Mary; Munk, Rachel; et al. (Aging cell, 2023)
Changes in the transcriptomes of human tissues with advancing age are poorly cataloged. Here, we sought to identify the coding and long noncoding RNAs present in cultured primary skin fibroblasts collected from 82 healthy individuals across a wide age spectrum (22–89 years old) who participated in the GESTALT (Genetic and Epigenetic Signatures of Translational Aging Laboratory Testing) study of the National Institute on Aging, NIH. Using high‐throughput RNA sequencing and a linear regression model, we identified 1437 coding RNAs (mRNAs) and 1177 linear and circular long noncoding (lncRNAs) that were differentially abundant as a function of age. Gene set enrichment analysis (GSEA) revealed select transcription factors implicated in coordinating the transcription of subsets of differentially abundant mRNAs, while long noncoding RNA enrichment analysis (LncSEA) identified RNA‐binding proteins predicted to participate in the age‐associated lncRNA profiles. In summary, we report age‐associated changes in the global transcriptome, coding and noncoding, from healthy human skin fibroblasts and propose that these transcripts may serve as biomarkers and therapeutic targets in aging skin.